Economic aspects of automation innovations in electronic transportation management systems - Jović, Marija, inženjerka pomorstva (Array, 2020)
This paper presents an analysis of economic aspects of three selected automation innovations in electronic Transportation Management Systems: Maritime Transport Chain solution and Vessel Estimated Time of Arrival solution (related to the maritime transport) and Delivery Planning solution (related to the transport in general). The theoretical background of transportation, Transportation Management Systems, maritime transportation and seaports is provided, focusing on the economic aspects. A literature review has been conducted, in order to identify the research gap and to focus on the economic aspects of the selected automation innovations. A SWOT Analysis of the Maritime Transport Chain solution, Vessel Estimated Time of Arrival solution and Delivery Planning solution (from an internal and external perspective) is presented, adding to the existing research of the economic aspects of automation innovations in the transport sector.